What Is New in Endometriosis?: Best Articles of the Past Year. Issue 4 (October 2018) - Stovall, Dale W.
Abstract : This month we focus on current research in endometriosis. Dr. Stovall discusses four recent publications, which are concluded with a "bottom-line" that is the take-home message. A complete reference for each can be found inBox 1 on this page along with direct links to the abstracts.